2012
DOI: 10.1007/s00265-012-1406-4
|View full text |Cite
|
Sign up to set email alerts
|

Contest behavior and other reproductive efforts in aging breeders: a test of residual reproductive value and state-dependent models

Abstract: Two models have been proposed to explain agerelated changes in reproductive performance. Statedependent models predict that reproductive effort depends on the magnitude of surplus energy reserves, which often varies with age. Contrary to this prediction, there was no significant effect of starvation on the outcome of contests for carcasses by female Nicrophorus orbicollis despite weight loss by starved females relative to controls. The residual reproductive value (RRV) model predicts that individuals adjust th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Female burying beetles also show terminal investment in postnatal care [28,54,55]. In female burying beetles, prenatal investment in offspring declines with age at first reproduction [28,56].…”
Section: Discussionmentioning
confidence: 99%
“…Female burying beetles also show terminal investment in postnatal care [28,54,55]. In female burying beetles, prenatal investment in offspring declines with age at first reproduction [28,56].…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the absence of conspecific competitors indicates a low population density, control females may have invested less in their current brood to take advantage of additional breeding opportunities in the future (McNamara et al 2009). An alternative explanation is that involvement in a contest might have resulted in injuries given the fierce competition over carcasses in Nicrophorus (Trumbo 1991;Cotter et al 2011), and injured females might have increased their investment in the current brood due to a higher risk of infection. A previous study on Nicrophorus vespilloides found that immunologically challenged females produced heavier broods than control females (Cotter et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We expected the mediumsized female to win the contest if she was paired with a small female, whereas we expected her to lose the contest if she was paired with a large female. We only used females that had been sexually mature for up to 2 weeks (i.e., 10-24 days after eclosion), because female age has been shown to influence contest outcome in the closely related Nicrophorus orbicollis (Trumbo 2012). At the start of the experiment, we transferred pairs of females to transparent plastic containers (17 cm # 12 cm # 6 cm) with 1 cm of moist soil and a freshly thawed mouse carcass of a standardized size (20-22 g).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests a specific deficit in muscle strength because other measures of health (ability to parent, lifetime reproductive success and longevity) are not affected. By contrast, Trumbo () found no effect of a 7‐day starvation period on contest ability when starvation begins on day 25, well after sclerotization and reproductive maturation are complete ( N. orbicollis ). At this stage of adult life, as in the present study, changes in body mass during starvation are likely to affect lipid reserves.…”
Section: Discussionmentioning
confidence: 99%